„Vlastní laboratoř“: akademické trajektorie a gender v současných biovědách. - Marcela Linková; Alice Červinková (Gender a Výzkum, 2013)
Despite various changes in academic institutions and the academic profession in last two decades (Shore 2008; Dunn 2003; Power 2003), the academic environment is still organized around the notion of a linear, uninterrupted career path (Murray 2000; Smithon and Stokoe 2005) culminating with the launch of one’s own lab. Rather than a remnant of previous organizing principles of science the linear notion of the academic career has been reordered and reinscribed in the recent science policy imaginary of the excellent career (Garforth, Červinková 2009). In light of the recent shifts in the organization of biosciences in the Czech Republic from dynastic to dynamic labs, the dominant ideologies of motherhood and the disembodied subject of the labour market, our goal in this paper is to contribute to feminist analyses of research careers and implications these recent shifts have in terms of the position of women- and especially mothers-bioscientists. Using the concept of enactment (Law 1994, Mol 2002) we examine the co-constitution of motherhood and research careers procesually, as a result of the effects of the gender order, science policy, family policy, institutional arrangements of research organizations and the personal. We wish to underscore the need for a complex study of research careers if we want to understand the nuanced ways in which gender is inscribed in careers in the biosciences.